Effect of organic matter and lime in remediation of heavy metals (Co, Ni & Pb) in Alfisols - Kumar, Rakesh; Kumar, R.; Rawat, K.S.; Yadav, Brijesh (Annals of Agricultural Research, 2014)
Soil samples differing in concentrations of heavy metals (Co, Ni and Pb) were categorized and five soil samples were taken under each categories viz., high, medium and low. Farm yard manure as organic matter @ 10 t/ha and quantity of lime were applied on the basis of lime requirement to raise the pH 6.4. Five replication of 15 samples with 36 treatments under completely randomized design were taken. These soils were incubated in laboratory for 60 days (0, 20, 40 and 60 days). Results revealed that lime was effective in reducing the availability of Co and Pb than that of organic matter and combined application of 50% organic matter + 50% lime, while in case of Ni, lime was significantly superior to organic matter but at par with combined application of 50% organic matter + 50% lime. A significant reduction in their availability was also observed with increasing incubation periods.